(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Soft tissue sarcomas (STS) are malignant tumours arising from mesenchymal tissue, comprising <1% of all the tumours of the human body and represent the second most common type of solid tumours in children and adolescents. Surgical resection is considered the mainstay of treatment, supported by multimodal therapies including chemotherapy and radiotherapy. Resource-limited countries, like Pakistan, face additional challenges due to inadequate resources. This study presents the experience of management of soft tissue sarcomas presenting to a tertiary care hospital in Central Lahore. Patients and methods: This was an observational study conducted in Surgical Unit I of Sir Ganga Ram Hospital Lahore from January 2017 till June 2022. American Joint Committee on Cancer (AJCC) staging system and Fédération Nationale des Centres de Lutte Contre le Cancer (FNCLCC) resection classification was applied. Surgical treatment including R0, R1 and R2 resections were carried out. SPSS 23 version was used for statistical analysis of collected data. Results: A total of 36 patients; 24 male (66.7%) and 12 females (33.3%) were included. Anatomical site involvement was observed as 23 (63.8%) limb sarcomas and 13 (36.1%) trunk sarcomas. Out of 36 patients, 20 (55.6%) patients were staged as stage II, 11 (30.5%) patients as stage III and 5 (13.9%) as stage I. Total 17 (47.2%) patients underwent wide excision, 13 (36.1%) patients underwent limited excision, 4 (11.1%) patients underwent compartmental excision and 2 (5.6%) patients underwent palliative excision. Recurrence was observed in 8 patients for which palliative 2 (5.6%), limited 3 (8.3%) or potentially curative resection 3 (8.3%) was performed. Conclusion: Thigh was the commonest site of involvement in extremity sarcomas. Retroperitoneal sarcomas were most frequent among trunk tumours. Leiomyosarcoma was the most common histopathological diagnosis followed by malignant peripheral nerve sheath tumours. Most of the patients presented with stage II disease. Resectional surgery, whether curative or palliative, was found to be the management modality of choice. Rhabdomyosarcoma most frequently recurred within 6 months of potentially curative surgery (R1), most likely due to compromised initial resection.